Low Vitamin D Level in Saudi Women With Polycystic Ovary Syndrome - Bindayel, Iman Abdullah (Frontiers in Nutrition, 2021)
Abstract: Polycystic ovary syndrome (PCOS) is a common endocrine disorder in women of reproductive age. In this study, serum 25-hydroxyvitamin D levels were compared between women with and without PCOS and with regard to anthropometric indices and lipid and glucose biomarkers. Thirty-one women with PCOS and 75 controls answered a questionnaire on vitamin D, in addition to general health and lifestyle. The patients with PCOS had lower vitamin D levels (p < 0.05), a significantly higher rate of obesity (p < 0.05), and significantly higher serum triglyceride levels than did controls. The number of patients with PCOS consumed milk and dairy products (p < 0.05) and exposed to sun (p < 0.006) were lower compared to controls. . Triglyceride levels were significantly correlated with body mass index (BMI); vitamin D level was not significantly correlated with anthropometrical or biochemical variables. These results affirm that vitamin D levels are lower in women with PCOS; however, despite the significantly higher proportion of obesity among patients with PCOS, hypovitaminosis was not associated with BMI. The relationship between body composition and vitamin D in PCOS and the effect of vitamin D correction on metabolic and hormonal parameters associated with PCOS must be assessed in future trials.